Loss-of-Function Mutations in CsMLO1 Confer Durable Powdery Mildew Resistance in Cucumber (Cucumis sativus L.) - Nie, Jingtao; Wang, Yunli; He, Huanle; Guo, Chunli; Zhu, Wenying; Pan, Jian; Li, Dandan; Lian, Hongli; Pan, Junsong; Cai, Run (Frontiers in Plant Science, 2015)
Powdery mildew (PM) is a serious fungal disease of cucumber worldwide. The identification of resistance genes is very important for resistance breeding to ensure cucumber production. Here, natural loss-of-function mutations at an MLO homologous locus, CsMLO1, were found to confer durable PM resistance in cucumber. CsMLO1 encoded a cell membrane protein, was mainly expressed in leaves and cotyledons, and was up-regulated by PM at the early stage of host-pathogen interaction. Ectopic expression of CsMLO1 rescued the phenotype of the PM resistant Atmlo2 Atmlo12 double mutant to PM susceptible in Arabidopsis. Domesticated and wild resistant cucumbers originating from various geographical regions of the world were found to harbor three independent natural mutations that resulted in CsMLO1 loss of function. In addition, between the near-isogenic lines (NILs) of PM resistant and susceptible, S1003 and NIL(Pm5.1), quantitative RT-PCR revealed that there is no difference at expression levels of several genes in the pathways of ethylene, jasmonic acid or salicylic acid. Moreover, the two NILs were used for transcriptome profiling to explore the mechanism underlying the resistance. Several genes correlated with plant cell wall thickening are possibly involved in the PM resistance. This study revealed that loss of function of CsMLO1 conferred durable PM resistance, and that this loss of function is necessary but alone may not be sufficient for PM resistance in cucumber. These findings will facilitate the molecular breeding of PM resistant varieties to control this destructive disease in cucumber.